Association between tocilizumab treatment of hyperinflammatory patients with COVID-19 in a critical care setting and elevated incidence of hospital-acquired bacterial and invasive fungal infections. (August 2022) - Minihan, B.; McAuliffe, E.; Powell, J.; Wong, S.L.; Wilkie, K.; Murphy, C.; Maher, A.; Power, L.; O'Connell, N.H.; Dunne, C.P.
Summary: Background: Tocilizumab is an interleukin-6 inhibitor that reduces mortality and the need for invasive mechanical ventilation, while increasing the possibility of successful hospital discharge for hyperinflammatory patients with severe coronavirus disease 2019 (COVID-19). No increase in adverse events or serious infections has been reported previously. Aim: To describe the characteristics and outcomes of patients with severe COVID-19 in critical care who received tocilizumab, and to compare mortality and length of hospital stay for patients who received tocilizumab ( N =41) with those who did not ( N =33). Methods: Retrospective review of data related to patients with COVID-19 who received tocilizumab in a critical care setting from 1 st January to 31 st December 2021. Findings: Amongst COVID-19 survivors, those who had received tocilizumab had longer intensive care unit (ICU) stays (median length 21 vs 9 days) and hospital stays (45 vs 34 days) compared with those who had not received tocilizumab. Thirty-day mortality (29% vs 36%; P =0.5196) and 60-day mortality (37% and 42%; P =0.6138) were not significantly lower in patients who received tocilizumab. Serious bacterial and fungal infections occurred at higher frequency amongst patients who received tocilizumab [odds ratio (OR) 2.67, 95% confidence interval (CI) 1.04–6.86; P =0.042], and at significantly higher frequency than in non-COVID-19 ICU admissions (OR 5.26, 95% CI 3.08–9.00; P <0.0001). Conclusions: In this single-centre study, patients in critical care with severe COVID-19 who received tocilizumab had a greater number of serious bacterial and fungal infections, but this may not have been a direct effect of tocilizumab treatment.